Comparative Price Analysis of Biological Products for Treatment of Rheumatoid Arthritis - Manova, Manoela; Savova, Alexandra; Vasileva, Maria; Terezova, Silvia; Kamusheva, Maria; Grekova, Daniela; Petkova, Valentina; Petrova, Guenka (Frontiers in Pharmacology, 2018)
The aim of this study was to conduct comparative price analysis of biological products for rheumatoid arthritis therapy among seventeen EU countries. The point of view is that of the Bulgarian pricing and reimbursement system and the chosen countries are those from reference basket. All authorized biological products by EMA with therapeutic indication rheumatoid arthritis were selected. The access for treatment is evaluated as the availability of the product on the market and the prices level. We assessed the availability of all trade names in the price lists of the observed countries. The prices data was obtained from the official web pages of the responsible institutions up to date December 2017. The results show that four out of all six INNs have authorized biosimilars. Despite its earlier authorization biosimilar adalimumab is not present in any of the price lists. From all eighteen countries only in Lithuania and Estonia there were no published prices of any of the selected medicinal products. Countries with higher number of biosimilar prices are Spain and France. Differences in manufacturers’ prices of reference biological products in selected countries in comparison with the lowest manufacturer price are higher with 22% to 69% while the retail prices between 62% and 95%. Differences are mostly notable for rituximab, and less notable for tocilizumab. Manufacturers’ and retail prices of biosimilar products were established only for 3 INNs (etanercept, rituximab and infliximab). Manufacturers’ prices differ between 26 % and 75%, while retail prices differ between 40% and 92% for biosimilars. Comparison of the differences between manufacturer prices of reference biological product and biosimilars shows 36% difference for etanercept, 39% for rituximab, and 31% for infliximab, while at retail level the differences are 11%, 86%, and 143% respectively. The limitation of the study is that the prices are the official ones without discounts due to confidentiality. Introduction of biosimilars on the national markets led to significant decrease in reimbursed prices paid by public funds and thus might benefit the patients’ access to biological therapy. The decrease of prices after biosimilars entrance on the market is not as notable as for commodity generics.